2021
DOI: 10.3389/fphys.2021.638868
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic Profiling of At-Risk Low and Very Low Birth-Weight Infants Using Magnetic Resonance Imaging

Abstract: Low birth-weight (LBW) and very low birth-weight (VLBW) newborns have increased risks of brain injuries, growth failure, motor difficulties, developmental coordination disorders or delay, and adult-onset vascular diseases. However, relatively little is known of the neurobiologic underpinnings. To clarify the pathophysiologic vulnerabilities of such neonates, we applied several advanced techniques for assessing brain physiology, namely T2-relaxation-under-spin-tagging (TRUST) magnetic resonance imaging (MRI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…The calculated values of tCMRO 2 (0.52 mlO 2 ∕100 g∕min) were lower compared to previous studies: neonates in intensive care units at different gestational ages 20,21 (∼1.0 ml O 2 ∕ 100 g∕min) and healthy and non-sedated neonates aged between 35 and 42 gestational weeks (0.76 mlO 2 ∕100 g∕min, 18 0.60 mlO 2 ∕100 g∕min, 19 and 1.2 mlO 2 ∕100 g∕min 22 ). This difference can partly be explained by the fact that StO 2 overestimates cerebro-venous saturation due to the arterial contribution to the NIRS signal.…”
Section: For Conversion)contrasting
confidence: 77%
“…The calculated values of tCMRO 2 (0.52 mlO 2 ∕100 g∕min) were lower compared to previous studies: neonates in intensive care units at different gestational ages 20,21 (∼1.0 ml O 2 ∕ 100 g∕min) and healthy and non-sedated neonates aged between 35 and 42 gestational weeks (0.76 mlO 2 ∕100 g∕min, 18 0.60 mlO 2 ∕100 g∕min, 19 and 1.2 mlO 2 ∕100 g∕min 22 ). This difference can partly be explained by the fact that StO 2 overestimates cerebro-venous saturation due to the arterial contribution to the NIRS signal.…”
Section: For Conversion)contrasting
confidence: 77%
“…For the studies that reported age in gestational weeks, CBF of the whole brain appeared to be much higher—ranging from 17 to 90 mL/100 g/min in subjects aged between 34 and 114 gestational weeks 37,40 . Several studies included both full and early‐term infants and demonstrated that CBF in pre‐term infants was significantly lower than those born in full‐term 34,37,44 . Regarding the factors affecting CBF in infants, only one study found that CBF (ranging between 17 and 90 mL/100 g/min) measured by PC MRI increased with age among infants between 34 and 114 gestational weeks at the time of scan 37 …”
Section: Resultsmentioning
confidence: 99%
“…Since some of these studies included CBF values in pre-term infants, we have found that whole brain CBF in full-term infants was generally higher than those born pre-term measured by ASL and PC MRI. 34,37,39,44 Taken together, the CBF alterations between birth and early adulthood may reflect energy consumption during different stages of brain development, both structurally and cognitively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation